Pengaruh Promosi Terhadap Keputusan Pembelian Produk Scarlett Whitening Dengan Kepercayaan Pelanggan Sebagai Variabel Mediasi Pada Pengguna Shopee Di Desa Keramas Kabupaten Gianyar - Ni Kadek Ariyanti; I Gusti Putu Agung Widya Goca; Cokorda Istri Agung Vera Nindia Putri (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Technological advancements in the Society 5.0 era have accelerated the growth of Indonesia’s e-commerce industry, including in Keramas Village, Gianyar Regency. Shopee, as the leading platform, makes it easier for users to shop, especially for local skincare products like Scarlett Whitening. The brand is well-known for its active promotional strategies on social media and collaborations with influencers. This study aims to examine the effect of promotion on purchase decisions with customer trust as a mediating variable among Shopee users in Keramas Village. This quantitative study used a survey method by distributing questionnaires to 120 respondents selected through purposive sampling. The population consisted of all Shopee users in the village. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The findings show that promotion has a positive and significant effect on customer trust, which in turn significantly affects purchase decisions. Furthermore, customer trust significantly mediates the effect of promotion on purchase decisions. The study provides important insights for businesses to design promotional strategies that not only attract customers but also foster long-term trust.